2008
DOI: 10.1039/b719706n
|View full text |Cite
|
Sign up to set email alerts
|

Controlling cell morphology on amino acid-modified cellulose

Abstract: This study shows that it is possible to affect the morphology and spreading of fibroblast cells on amino acid-modified cellulose-based fibrous networks. Hydrophilic (Gly, Ser), aliphatic (Ala, Val, Leu, Ile) and aromatic amino acids (Phe, Tyr, Trp), coupled to the cellulose via esterification, give rise to different cell morphologies. Modified cellulosic substrates are analysed using time of flight secondary ion mass spectrometry (TOF-SIMS), demonstrating that amino acids are coupled and uniformly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…An invariant Fmocprotected water contact angle was observed, and a correlation of the water contact angle with the side chain hydrophobicity was reported after Fmoc deprotection (Rawsterne et al 2007). In contrast to this, our previous study reported a variable water contact angle for different Fmoc-amino acid modified celluloses, suggesting variable levels of coupling (Kalaskar et al 2008). However, in the work of Rawsterne et al (2007) a quantitative analysis of chemical modification was not reported, and thus information on single amino acids coupling on glass coverslips is not available.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…An invariant Fmocprotected water contact angle was observed, and a correlation of the water contact angle with the side chain hydrophobicity was reported after Fmoc deprotection (Rawsterne et al 2007). In contrast to this, our previous study reported a variable water contact angle for different Fmoc-amino acid modified celluloses, suggesting variable levels of coupling (Kalaskar et al 2008). However, in the work of Rawsterne et al (2007) a quantitative analysis of chemical modification was not reported, and thus information on single amino acids coupling on glass coverslips is not available.…”
Section: Discussionmentioning
confidence: 65%
“…However, we have shown in a previous study that after chemical coupling with Fmoc-protected amino acids, surface hydrophobicity increases significantly (Kalaskar et al 2008). Rawsterne et al (2007) coupled Fmoc-protected amino acids on glass coverslips.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The explanation of the phenomenon is complicated, however, by the chemical, topographical and possibly mechanical heterogeneity of the surfaces, with both cellulose and PAHCl-coated glass regions presented to the cells. As both PAHCl and model cellulose-I surfaces have been reported elsewhere to support cell adhesion and serum protein adsorption, it seems unlikely that the chemical heterogeneity of the surfaces is responsible for modulating cell adhesion leading to bulk contact guidance and orientation [12,[32][33][34]. We therefore postulate that the anisotropic nanoscale topography or mechanical properties of the adsorbed CNW surfaces induce contact guidance in the C2C12 myoblasts.…”
Section: Morphology Of C2c12s On Cnw Surfacesmentioning
confidence: 89%
“…Chemical cues that emulate the ECM environment and potentially tune the cell phenotypic state were incorporated in the form of cellulose nanocrystals (CNCs) [33,34] that carry a small number of sulfate (S-CNCs, 98.5 ± 8.2 mmol/Kg) or phosphate (P-CNCs, 10.1 ± 1.6 mmol/Kg) ester groups on their surface (Supporting Information Figure S1). The dimensions of the nanocrystals were determined to be 200 ± 54 nm in length and 25 ± 4 nm in diameter for S-CNCs and 199 ± 56 nm and 23 ± 5 nm for PCNCs (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%